Anomalous Hall transport in tilted multi-Weyl semimetals. (28th October 2020) - Menon, Anirudha; Basu, Banasri
Abstract: We study the effect of a perpendicular magnetic field B on a multinode Weyl semimetal (mWSM) of arbitrary integer monopole charge n, with the two Weyl multinodes separated in k -space. Besides type-I mWSMs, there exist type-II mWSMs which are characterized by the tilted minimal dispersion for low-energy excitations; the Weyl points in type-II mWSMs are still protected crossings but appear at the contact of the electron and hole pockets, after the Lifshitz transition. We find that the presence of a perpendicular magnetic field quantizes the occupation pockets due to the presence of Fermi tubes. In this theory, the Hilbert space is spanned by a set of n chiral degenerate ground states, and a countably infinite number of particle-hole symmetric Landau levels (LLs). We calculate the Hall conductivity for the tilt-symmetric case of type-I mWSM using the Kubo formula, in the zero-frequency (DC) limit, and recover the well-known vacuum contribution. We compute the Fermi surface corrections and show that the expression generalizes from the formula for elementary ( n = 1) type-I WSMs. We derive an expression for the type-II mWSM Hall conductivity, which is bounded by a LL cutoff introduced on physical grounds. Interestingly, we find that the anomalous vacuum Hall conductivity is vanishing in the type-II phase at all temperatures. The corresponding thermal Hall and Nernst conductivities are evaluated and characterized for both phases. The qualitative and quantitative observations presented here may serve in the characterization of generic mWSMs of both types.